Novas tecnologias em vigilância em saúde: desenvolvimento e uso de aplicativo móvel para a notificação, controle e vigilância da leishmaniose visceral canina - Vasconcellos, Jaíne Soares de Paula (2021)
Health technologies are present in all stages of the health-disease process, from prevention to treatment and health recovery. Visceral leishmaniasis (VL) is the most severe form of a complex of human and animal diseases, endemic in more than 70 countries. Regarding collective health, it is essential to develop and offer technologies capable of increasing the resolution capacity of control programs for this zoonosis. Data analysis and the construction of health indicators depend on the ability of disease notifications to epidemiological surveillance, which include data collection, storage, processing and retrieval. Georeferencing can become an important tool to help in the reading of the epidemiological situation of the regions, as well as in the planning and interventions of future actions to control the disease. Thus, we sought to develop a tool capable of assisting professionals involved with VL in reporting positive cases of the disease to the public health system. In addition, active search actions and epidemiological surveys were carried out in partnership with the Municipal Environmental Surveillance. Through new information technologies, the Application (App) C7-LVC was developed, characterized by a system that has the capacity to store data related to the notification of canine visceral leishmaniasis (LVC). The App performs georeferencing of the reported data, stores photographic records and generates reports, in addition to enabling complex spatial analysis, as it enables the integration of data from different sources. This system allows the manipulation of large volumes of data, enabling the quick and secure recovery of information stored in the database. The App can be used as an individual tool or by health surveillance services and can help carry out epidemiological surveys and investigation of cases of the disease. The C7 LVC was tested in the city of Santa Maria, Rio Grande do Sul and its use could be expanded to the entire national territory. The transfer of this technology to SUS can contribute to the improvement of health information and streamline decision-making by managers involved in VL control. The important social role of the partnership between the University and the health system and the effective contribution to the consolidation and strengthening of the SUS is highlighted.